Efficient Extraction of Methylene Blue from Aqueous Solution Using Phosphine-Based Deep Eutectic Solvents with Carboxylic Acid - Hassan, Muhammad Faheem (2022)
Methylene blue (MB), an organic thiazine dye, has numerous industrial and medical applications. However, MB is a wastewater contaminant that is harmful to humans and aquatic life. Hence, its removal from water bodies is essential. In this work, five novel deep eutectic solvents (DESs) were synthesized using different precursors, screened, and studied for the extraction of methylene blue (MB) from aqueous solution using liquid–liquid extraction. The first, TOP-SA, was synthesized using trioctylphosphine (TOP) as a hydrogen bond acceptor (HBA) and 2-hydroxy benzoic acid as a hydrogen bond donor (HBD). Among these, TOP-SA had the highest MB removal efficiency. The effects of pH, contact time, initial MB concentration, volumetric ratio, temperature, and ionic strength were studied and optimized. A 99.3% removal was achieved in 5 min for a 200 mg dm−3 MB solution mixed in a 1:10 ratio with TOP-SA at 25.0 °C. The structural properties of TOP-SA and its interactions with MB were investigated using FTIR. TOP-SA’s toxicity was investigated using human cells in vitro. TOP-SA was found to be comparatively less toxic and is a more efficient MB remover than other literature reported ionic liquids (ILs).